Theoretical Approaches for Electron Transport Through Magnetic Molecules - Aravena-Ponce, D; Aravena-Ponce, D (Springer Science and Business Media B.V., 2023)
Compared to conventional silicon-based electronic systems, molecular devices based on spin properties open up a much wider range of possibilities. The use of magnetic molecules as active components in these devices paves the way for the design of new spin-based devices, even controlling single spin centers. For instance, magnetic materials have been proposed as components to build spin valves in which the relative orientation of the magnetization between the electrodes controls the electron transport. Taking advantage of the broad toolkit of chemistry, molecules can be attached to electrodes via linking groups in order to confer robustness to molecule-based devices and increase conductivity. The interest in creating ever more complex molecular devices has been accompanied by significant advances in our theoretical understanding of the electron and spin-transfer phenomenon. The atomistic description of molecular devices is inherently complex due to their increased size in comparison with molecular systems, the combination of components with contrasting electronic structure, and the non-equilibrium nature of the transport problem. Furthermore, the description of spin-polarized systems poses new challenges to the theory, as accurate spin-dependent energetics are difficult to achieve, and the wavefunctions associated with magnetic states can be qualitatively more complex than the closed-shell solutions used for non-magnetic systems. In this chapter, we review molecular-based spintronic devices and the current approaches for modeling electron and spin transport in magnetic systems. Special attention is devoted to systems based on single-molecule magnets (SMMs) and on the emerging interest in the interplay between spin and chirality for the design of new spintronic devices. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.